FOREIGN EXCHANGE BANK SERVICE DEVELOPMENT STRATEGY AT BANK SULSELBAR - Muhammad Asril Azis; Nurdin Brasit; Abdul Rakhman Laba (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
The right strategy is needed for the development efforts of a company. This research aims to identify the internal environment in the form of strengths and weaknesses that affect the development of foreign exchange bank services at Bank Sulselbar; Identifying the external environment in the form of opportunities and threats that affect the development of foreign exchange bank services at Bank Sulselbar, and analyze and formulate a strategy for the development of foreign exchange bank services at Bank Sulselbar. This research is designed with quantitative form and uses survey methods aimed at analyzing internal and external factors that can support the development of Bank Sulselbar as a Foreign Exchange Bank. The results showed the position of Bank Sulselbar's foreign exchange service development strategy was in Kuadaran I (first) which is an aggressive strategy by implementing the SO (Strenght-Opportunity) strategy. The aggressive strategy that is a priority in the development of foreign exchange services for Bank Sulselbar shows that with the support of shareholders, a strong network, and reliable technology, the development of Bank Sulselbar's foreign exchange services should be optimized so as to provide strategic value for the sustainability of Bank Sulselbar's business development.